2020
DOI: 10.3390/fluids5020053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polypropylene Fibers and Measurement Methods on the Yield Stress of Grouts for the Consolidation of Heritage Masonry Walls

Abstract: The injection of grouts is a consolidation technique suitable for overcoming the structural deterioration of old stone masonry walls. Grouting operations involve introducing a suspension (grout) into a masonry core with the aim of improving the load capacity of the wall, as well as reducing its brittle mechanisms. The yield stress of injection grouts will affect the injection pressure and their flow inside the masonry. However, the determination of some rheological properties such as yield stress in hydraulic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…The result of the mortar test supports the finding of some other studies where the addition of polypropylene fiber can increase the quality of the mortar and reinforced concrete [24]- [28]. Polypropylene fiber can increase the mortar and reinforced concrete properties towards dynamic load [29], [30][31], [32].…”
Section: A Compressive Strengthsupporting
confidence: 83%
See 1 more Smart Citation
“…The result of the mortar test supports the finding of some other studies where the addition of polypropylene fiber can increase the quality of the mortar and reinforced concrete [24]- [28]. Polypropylene fiber can increase the mortar and reinforced concrete properties towards dynamic load [29], [30][31], [32].…”
Section: A Compressive Strengthsupporting
confidence: 83%
“…The maximum deflection was seen reaching 20.49 mm for DBPP with a maximum load of 8.27 kN. Some previous studies of strengthening of masonry brick that uses polypropylene material have shown an improvement of masonry properties also [8], [32], [34]- [36]. As mortar or concrete can endure high temperatures [37], the addition of polypropylene can increase the capacity of mortar or concrete with polypropylene towards temperature load [38].…”
Section: B Flexural Strengthmentioning
confidence: 99%
“…[8,9]. Most scholars in the industry [10][11][12][13][14] believe that there is an optimal dosage of retarder, and its type also has a great impact on the quantitative and mechanical indexes of grouting. Relevant researches have also obtained some important conclusions on the effects of inorganic and organic retarders on the properties of grouting materials.…”
Section: Introductionmentioning
confidence: 99%
“…The Special Issue "Advances in Experimental and Computational Rheology, Volume II" comprises 10 papers covering some of the latest advances in the fields of experimental and computational rheology, applied to a diverse class of materials and processes, which can be grouped into three main topics: rheology [1][2][3][4][5], rheometry and processing [6,7], and theoretical modeling [8][9][10].…”
mentioning
confidence: 99%
“…The characterization of rheological behavior is the main topic of five contributions, covering the following materials/systems: S-aureus cultures (Portela et al [1]), in which antibiotic activity was screened by rheometry; natural hydraulic lime grouts filled with polypropylene fibers (Baltazar et al [2]), with a particular focus on the effect of the measurement methods on the obtained yield stress; wheat flour dough (Macedo et al [3]), where rheology was used as a tool to study the impact of whey powder addition on the dough and breadmaking performance; human milk (Alatalo et al [4]), covering the influence of external factors on its characteristics; and graphene oxide/poly(ethylene glycol) suspensions (Soares et al [5]), where the authors studied the influence of the oxidation degree of graphene oxide on the suspensions' shear rheology.…”
mentioning
confidence: 99%